Transformable nanoparticles triggered by cancer-associated fibroblasts for improving drug permeability and efficacy in desmoplastic tumors. Issue 42 (15th October 2019) - Hou, Lin; Chen, Dandan; Hao, Lisha; Tian, Chunyu; Yan, Yingshan; Zhu, Ling; Zhang, Huijuan; Zhang, Yi; Zhang, Zhenzhong
Abstract : Cancer-associated fibroblasts (CAFs) are important barriers for nanoparticles (NPs) to deeply penetrate into tumors and severely limit the antitumor efficacy of nanomedicines. Abstract : Cancer-associated fibroblasts (CAFs) are important barriers for nanoparticles (NPs) to deeply penetrate into tumors and severely limit the antitumor efficacy of nanomedicines. Herein, we proposed a CAF-triggered transformable drug delivery system based on a cleavable peptide responsive to fibroblast activation protein-α (FAP-α) specifically overexpressed on the surface of CAFs. The NPs were composed of cationic poly(amidoamine) (PAMAM) dendrimers cross-linked by our designed peptide, a chemotherapeutical drug was incorporated onto PAMAM using disulfide bonds and finally, hyaluronic acid (HA) was conjugated to improve the tumor targetability as well as biocompatibility through electrostatic interactions. These NPs had an initial size of ∼200 nm and negative zeta potential favorable for stable blood circulation; however, after docking with CAFs, they dissociated into smaller NPs and exposed the relative positive surface charge to facilitate penetration and enter the tumor cells together with CAFs. An interesting finding was that this system intracellularly released different levels of drugs in these two kinds of cells, which was beneficial for the disruption of the stromal barrier and increasing the local drug accumulation. Our investigation confirmed that the constructed system could alleviate the biological barriers and hold promising therapeutic efficiency for desmoplastic solid tumors.